ПРАВО НА ЖИЗНЬ КАК НЕОТЪЕМЛЕМОЕ ПРАВО ГРАЖДАН, ОСУЖДЁННЫХ К ЛИШЕНИЮ СВОБОДЫ В УКРАИНЕ: СОДЕРЖАНИЕ И АДМИНИСТРАТИВНОПРАВОВОЕ ОБЕСПЕЧЕНИЕ - Почанская, Елена Сергеевна (SUPREMANCE OF LAW, 2018)
The main scientific approaches to understanding and classification ofthe natural human rights andfreedoms are considered. The content and specific features of Right to Life of a persons condemned to imprisonment are determined. Analyzes ofthe contemporary situation of administrative-legal ensuring of Right to Life of persons condemned to imprisonment in Ukraine were prepared.